(untitled) (Bangladesh Pharmaceutical Journal, 2022)
Piper methysticum G. Forst., commonly known as Kava, is a dioecious perennial herb which is traditionally an important medicinal plant. The plant is used to treat fever, respiratory diseases, seizures, and urogenital problems. The present study was designed to evaluate the antioxidant, cytotoxic, membrane stabilizing and analgesic potential of methanol extract of Piper methysticum leaf. Phytochemical screenings of the crude extract revealed the occurrence of acidic compounds, alkaloids, glycosides, reducing sugars, gums, flavonoids, and combined reducing sugars. During antioxidant activity test, the total phenolic content of methanol extract was 42.66 mg gallic acid equivalent/100 g extract and it displayed the IC50 value of 6.59 μg/ml to remove DPPH free radicals as compared to the standard butylated hydroxyl toluene (IC50 = 6.38 μg/ml). The extract showed cytotoxicity against brine shrimp nauplii with an LC50 of 60.94 μg/ml. Moreover, the test extract was found to be effective for stabilizing erythrocyte membrane against hypotonic solution induced hemolysis. The extract exhibited dose-dependent pain-relieving activity in mice. At doses of 250- and 500-mg/kg body weight, the plant sample revealed 26.9 2% and 37.95 % of reduction in pain sensation induced by acetic acid, respectively when compared to the standard diclofenac-Na (54.81%). The above results suggest that the selected plant extract possesses antioxidant, cytotoxic, membrane stabilizing and analgesic activities. Bangladesh Pharmaceutical Journal 25(1): 73-79, 2022 (January)